Response of oil and protein content to seed size in cotton(Gossypium hirsutum L., cv. Sahel). - Pahlavani, M. H.; Miri, A.A.; Kazemi, G. (Plant Breeding and Seed Science, 2009)
This study was designed to identify the response of oil and protein content to non-heritable variation of seed size in cotton (Gossypium hirsutum L.). The experiment was conducted at Gorgan University of Agricultural Sciences, Gorgan, Iran in 2005. The results showed that germination and emergence increased linearity with seed size and R2 of these relationships were 92 and 89%, respectively. This means that larger seed had higher potential of germination and emergence. Also, there was a strong linear relationship between seed weight and oil content. Seed weight provided a better indication of oil content (R2=0.78) than protein content (R2=0.43). There are no considerable relationship between seed size and protein content of seed...